Rotary Club: poder invisível na Terra Prometida: (1959-1967) - Lacerda, Renato Santos (2007)
In this research, the spotlights are aimed on the historical years between 1959 and 1967, with the main purpose of showing the scenic arrangements of the installation, organization and performance of a Rotary Club in a geographical scenery that was in mutation phase. That territory, formerly denominated Promised Earth or Canaan of the Industry, was soon substituted by the nomenclature Steel Valley .The partners founders of that first Rotary Club conceived themselves as foreigners from the Canaan of the State of Minas that emanated "milk and honey". Native from another lands, they met each other and they were met in order to form a service club in the Nacional Valley of Redemption, but with intense institutional entails to an international corporation. Organized under the doctrine of the interest well understood, the associated agents, each one, with his composition and capital volume, of economic, cultural, social, symbolic or political nature, they allowed, through the mechanism of capital convertibility, to concentrate, in the regional community, a power, capable to produce real effects without apparent waste of energy. As a voluntary and oligarchical association, this service club was, in a way, a institutional vehicle, in the local sphere, of appropriation, incorporation, reproduction and diffusion of visions of world of the ideological corpus of International Rotary.